2002
DOI: 10.1095/biolreprod66.5.1548
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leptin and Its Receptor in the Murine Ovary: Possible Role in the Regulation of Oocyte Maturation1

Abstract: Leptin is a product of the ob gene that is produced primarily by adipose tissue. Leptin and its receptors are found within the ovary, but it is unclear what function this hormone has in the ovary. Using immunohistochemistry, we determined that leptin is found in most cell types in the murine ovary, with the highest staining levels observed in the oocyte. Leptin receptor was also expressed in all of the main ovarian cell types, with the thecal cell layer exhibiting the highest staining levels. Leptin administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 34 publications
5
91
1
4
Order By: Relevance
“…Leptin receptor mRNA and protein is expressed in mouse oocytes [7,8] and leptin induces tyrosine phosphorylation of STAT3, a major intracellular leptin signal transduction protein, in mouse metaphase 2 stage oocytes [8]. Ryan and co-workers [7] reported that leptin enhances resumption of meiosis in preovulatory follicle-enclosed oocytes in culture, but does not alter meiotic resumption in denuded or cumulus-enclosed oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin receptor mRNA and protein is expressed in mouse oocytes [7,8] and leptin induces tyrosine phosphorylation of STAT3, a major intracellular leptin signal transduction protein, in mouse metaphase 2 stage oocytes [8]. Ryan and co-workers [7] reported that leptin enhances resumption of meiosis in preovulatory follicle-enclosed oocytes in culture, but does not alter meiotic resumption in denuded or cumulus-enclosed oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Ryan and co-workers [7] reported that leptin enhances resumption of meiosis in preovulatory follicle-enclosed oocytes in culture, but does not alter meiotic resumption in denuded or cumulus-enclosed oocytes. Leptin receptor is expressed in mouse 1-cell and 2-cell embryos as well as morulae and blastocysts [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While leptin correlates with progesterone concentrations throughout the cycle [61], LEPRs in oocytes might also influence oocyte maturation and development [62]. In fact, in mouse oocytes [63][64][65] leptin induces tyrosine phosphorylation of STAT3, a major intracellular leptin signal transduction protein in mouse metaphase II stage oocytes [64]. Moreover, LEPR and leptin mRNA is specifically expressed at the blastocyst stage, suggesting a function in the blastocyst-endometrial dialog [8].…”
Section: Role Of Leptin In Preinplantational Embryomentioning
confidence: 99%
“…The ovary is also believed to be a site of leptin synthesis. The presence of leptin mRNA and protein was observed in human GC and theca cells, follicular fluid, oocytes and CL Cioffi et al, 1997;Loffler et al, 2001;Welt et al, 2003), in murine GC and theca cells, oocytes, CL and OS Ryan et al, 2002 andArchanco et al, 2003) and in porcine CL and OS (Smolinska et al, 2010). The expression of leptin and OB-Rb in porcine ovarian follicles during the cycle and in early pregnancy (implantation) has scarcely been investigated to date.…”
Section: Introductionmentioning
confidence: 99%